Key Features of Australian Business Cycles - Cashin, Paul.; Ouliaris, Sam. (Washington, D.C. : International Monetary Fund, 2001)
This paper identifies and describes the key features of Australian business cycles during 1959-2000. In particular, we identify the chronologies in Australia's classical cycle (expansions and contractions in the level of output) and growth cycle (periods of above-trend and below-trend rates of economic growth). We find that while there are large asymmetries in the duration and amplitude of phases in Australia's classical cycle, on both measures the Australian growth cycle is much more symmetric. Further, our results indicate that over the sample period Australian (filtered) output and prices have moved in a counter-cyclical fashion, suggesting a dominance of shocks to aggregate supply affecting the Australian economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Growth Cycle; Null Hypothesis; Price Level; Rank Correlation; WP; Australia